Association of undernutrition and female infertility in East Africa: Finding from multi-country demographic and health surveys - Roba, Kedir Teji; Hassen, Tahir Ahmed; Wilfong, Tara; Legese Alemu, Nanati; Darsene, Hiwot; Zewdu, Gelila; Negese, Tarekegn; Yifru, Belaynesh; Mohammed, Eptisam; Raru, Temam Beshir (Frontiers in Global Women's Health, 2022)
Introduction: Infertility is one of the public health problems affecting a significant number of women in the reproductive age group. Although female fertility is predominantly affected by gynecological and systemic diseases, lifestyle and nutritional factors also play an important role in secondary female infertility. Therefore, this study aimed to determine the pooled prevalence of secondary female infertility and its association with undernutrition using nationwide data from the Demographic and Health Surveys (DHS) of eastern African countries. Methods: The data of ten East African countries that comprise a weighted sample of 38,020 women data were accessed from measure DHS. Data processing and analysis were performed using STATA 15 software. A multilevel mixed-effect logistic regression model was fitted to examine the association between undernutrition and secondary infertility. Variables with a p-value<0.05 were declared as significant factors associated with secondary infertility. Model comparison was done based on Akaike and Bayesian Information Criteria (AIC and BIC). To measure variation (random effects), Community-level variance with standard deviation and intra-cluster correlation coefficient (ICC) was used. Result: The proportion of women who have secondary infertility was 16.32% with 95%CI (15.96, 16.69), of which 26.94% were undernourished. This study found that being undernutrition (AOR=1.74; 95%CI:1.54-1.98) and overweight (AOR=1.72; 95%CI: 1.62-1.86) were significantly associated with secondary infertility. Women aged>35 years (AOR=3.47; 95%CI: 2.66-4.55), and rural residents (AOR=1.16; 95%CI: 1.02-1.37) are other factors that are positively associated with secondary infertility. However, primary education (AOR=0.87; 95%CI: 0.77-0.97) and richer wealth index (AOR=0.84; 95%CI:0.73-0.97) are protective factors for secondary infertility. Conclusion: This study indicated that there is a strong association between secondary infertility and undernutrition growing in Eastern Africa. Therefore, Health information dissemination and awareness creation on the impact of malnutrition on infertility should be given to the community and health care providers. Given this, it may lead to integrating nutrition counseling into both clinical settings for infertility management as well as national dietary guidelines for individuals of reproductive age.